Observations of gas- and aerosol-phase organic nitrates at BEACHON-RoMBAS 2011 - J. L. Fry; D. C. Draper; K. J. Zarzana; P. Campuzano-Jost; D. A. Day; J. L. Jimenez; S. S. Brown; R. C. Cohen; L. Kaser; A. Hansel; L. Cappellin; T. Karl; et al. (Atmospheric Chemistry and Physics, 2013)
At the Rocky Mountain Biogenic Aerosol Study (BEACHON-RoMBAS) field campaign in the Colorado front range, July–August 2011, measurements of gas- and aerosol-phase organic nitrates enabled a study of the role of NOx (NOx = NO + NO2) in oxidation of forest-emitted volatile organic compounds (VOCs) and subsequent aerosol formation. Substantial formation of peroxy- and alkyl-nitrates is observed every morning, with an apparent 2.9% yield of alkyl nitrates from daytime RO2 + NO reactions. Aerosol-phase organic nitrates, however, peak in concentration during the night, with concentrations up to 140 ppt as measured by both optical spectroscopic and mass spectrometric instruments. The diurnal cycle in aerosol fraction of organic nitrates shows an equilibrium-like response to the diurnal temperature cycle, suggesting some reversible absorptive partitioning, but the full dynamic range cannot be reproduced by thermodynamic repartitioning alone. Nighttime aerosol organic nitrate is observed to be positively correlated with [NO2] × [O3] but not with [O3]. These observations support the role of nighttime NO3-initiated oxidation of monoterpenes as a significant source of nighttime aerosol. Nighttime production of organic nitrates is comparable in magnitude to daytime photochemical production at this site, which we postulate to be representative of the Colorado front range forests.